Studi Mikrostruktur Mortar Geopolimer Abu Sawit dengan Variasi Rasio Na2SiO3 terhadap NaOH - Wari Dony; Amsori M Das (Universitas Batanghari Jambi, 2019)
In the context development of building materials geopolymer concrete is an environmentally technology. The goal of the study identifies and examines geopolymer concrete becoming alternative to portland cement (PC) as a construction material section is utilized as one of the local plantation industry waste such as oil palm ash. Polymerzation process performed the oil palm ash as precursor that contains high silicate calcium with Na2SiO3 and NaOH as alkali activator. Mix design is carried out by ratio of alkali activator 2,0. 1,5 and 1,0 at a concentration of NaOH 8, 10, 12, 14 and 16 M at temperature 90°C for 24 hours. The method used is the separate mixtures with extra water and mixed methods directly without extra water. The result show that the higher concentration of NaOH solution, the compressive strength is increased at level of 12,4 Mpa=8,4 M for the mortar with extra water and 20,2 Mpa= 16 M without extra water at ratio of 1,5 alkaline activators. The ratio mixture of alkali activator 1,0and 2,0 would produce a low compressive strength. Microstructure result shows that matrix is formed more solid at each increase in the concentration of Na OH solution. The ratio of Alkali activator 1,5 causing precursors and alkaline activators to react homogeneously so that the formed geopolymer matrix becomes more solid